2019
DOI: 10.3354/meps13049
|View full text |Cite
|
Sign up to set email alerts
|

Blue crab larval dispersal highlights population connectivity and implications for fishery management

Abstract: In the Western Atlantic and Gulf of Mexico (GOM), the blue crab Callinectes sapidus fishery is managed at a regional scale, and its assessment does not consider the population structure of the species. To understand connectivity of the blue crab population, we simulated larval dispersal using a biophysical model driven by high-resolution ocean currents and including early life-history traits of the species. Simulations were conducted during 2015 and 2016, and larvae were released from locations along Florida's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Trends in age-0 catch show that in most Florida estuaries, recruitment occurs year round to some degree, even though no spawning aggregations are present nearby. These results were confirmed by Criales et al (2019), who demonstrated that there was a high degree of larval retention during summer in Florida estuaries, accounting for age-0 abundance peaks in fall and winter. Criales et al (2019) also found evidence of connectivity between waters of other Gulf states, Florida waters, and the South Atlantic Bight.…”
Section: Blue Crab Spawning In Florida Estuariessupporting
confidence: 63%
“…Trends in age-0 catch show that in most Florida estuaries, recruitment occurs year round to some degree, even though no spawning aggregations are present nearby. These results were confirmed by Criales et al (2019), who demonstrated that there was a high degree of larval retention during summer in Florida estuaries, accounting for age-0 abundance peaks in fall and winter. Criales et al (2019) also found evidence of connectivity between waters of other Gulf states, Florida waters, and the South Atlantic Bight.…”
Section: Blue Crab Spawning In Florida Estuariessupporting
confidence: 63%
“…The large numbers of blue crab caught offshore of Louisiana relative to catch in other regions likely reflect the low salinities present in estuaries of Louisiana. Egg hatching and larval survivorship is negatively affected by salinities <20.1 (Costlow and Bookhout, 1959); during the spawning migration, therefore, females move to spawning grounds suitable for offspring survival. It is possible that the low salinities in estuaries of Louisiana result in greater numbers 9 NMFS (National Marine Fisheries Service).…”
Section: Discussionmentioning
confidence: 99%
“…After mating, female blue crab forage for several weeks (Turner et al, 2003) before beginning a seaward spawning migration (Aguilar et al, 2005). This migration ensures that females reach spawning grounds of sufficiently high salinity (>20.1; Costlow and Bookhout, 1959) for larval survival. Spawning female blue crab are often found in large numbers at or near the mouths of estuaries (e.g., Rittschof et al, 2010;Anderson et al, 2017); these areas are typically assumed to be the primary spawning grounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent modeling studies on virtual larvae have allowed detection of trajectories illustrating habitat connectivity. For example, Criales et al (2019) studied blue crab (Callinectes sapidus) showing variable larval dispersal pathways between 2015 and 2016, which were driven by the interaction of winds, the Mississippi River plume, Loop Current intrusions in the northern GoM, Loop Current eddies, and their cyclonic counterparts. Their findings supported the homogeneous genetic population structure of C. sapidus among Mid-Atlantic and GoM populations, as the Mississippi River plume provided a conduit to transport virtual larvae to the South Atlantic Bight.…”
Section: Opportunities For Conservation and Sustainabilitymentioning
confidence: 99%